RIF1 controls replication initiation and homologous recombination repair in a radiation dose-dependent manner - Saito, Yuichiro (J Cell Sci, 2020)
RIF1 controls both DNA replication timing and the DNA double-strand break (DSB) repair pathway to maintain genome integrity. However, it remains unclear how RIF1 links these two processes following exposure to ionizing radiation (IR). Here, we show that inhibition of homologous recombination repair (HRR) by RIF1 occurs in a dose-dependent manner and is controlled via DNA replication. RIF1 inhibits both DNA end resection and RAD51 accumulation after exposure to high doses of IR. Contrastingly, HRR inhibition by RIF1 is antagonized by BRCA1 after a low-dose IR exposure. At high IR doses, RIF1 suppresses replication initiation by dephosphorylating MCM helicase. Notably, the dephosphorylation of MCM helicase inhibits both DNA end resection and HRR, even without RIF1. Thus, our data show the importance of active DNA replication for HRR and suggest a common suppression mechanism for DNA replication and HRR at high IR doses, both of which are controlled by RIF1. This article has an associated First Person interview with the first author of the paper.